2013
DOI: 10.1155/2013/983250
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Look at Blood Transfusion Utilization in Total Joint Arthroplasty at a Single Academic Medical Center under a Single Surgeon

Abstract: The utilization of autologous and allogeneic transfusions in total joint arthroplasties was to characterize patients who may benefit from giving preoperative blood donations. We conducted a retrospective chart review of 525 patients to document preoperative hematocrit, estimated blood loss, length of stay, transfusions, and medical comorbidities. Results of our review showed that total hip arthroplasty revision (THA-R) had the highest prevalence of transfusions (60%) followed by total hip arthroplasty (THA, 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Therefore, we can predict possibly when patients will need to transfusion if we have basic Hb value. Robinson et al showed that intraoperative transfusion was highly related to primary hemoglobin [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we can predict possibly when patients will need to transfusion if we have basic Hb value. Robinson et al showed that intraoperative transfusion was highly related to primary hemoglobin [2].…”
Section: Discussionmentioning
confidence: 99%
“…Specialists have various opinions about this. This discrepancy leads to frequent and sometimes, unnecessary transfusions [1] [2]. Over decades, evidences showed that transfused patients expose with different adverse events (particularly, allogeneic blood) [1] [2] [3] [4] [5] such as postoperative pneumonia, sepsis and death [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that better models are necessary to predict which patients are at an increased risk for a blood transfusion during the perioperative period. The collected data suggest that the preoperative hematocrit is the most important factor when assessing the need for blood transfusion, additional variables including age, race, gender, BMI, and comorbidities ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple surveys addressed to Dutch and UK orthopedic surgeons within the last decade revealed an increased awareness and a positive attitude toward perioperative BSMs. The need for perioperative blood management directed toward improving patient outcome with reduced ABT is generally recognized ( 31 , 33 ). The hemoglobin threshold warranting transfusion continues to be debated among anesthesiologists and orthopedic surgeons ( 34 ).…”
Section: Introductionmentioning
confidence: 99%